2015
DOI: 10.1001/jamasurg.2014.2025
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Small Abdominal Aortic Aneurysm Expansion Rate

Abstract: Smoking cessation and control of diastolic blood pressure are direct actions that should be taken to reduce the rate of AAA expansion. Other clinical risk factors, except for diabetes, were not associated with the AAA expansion rate. This study also provides evidence of differing trajectories in AAA expansion over time, a finding that merits further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 25 publications
8
88
1
Order By: Relevance
“…Of them, we identifi ed seven eligible studies [9][10][11][12][13][14][15] reporting the association of BMI and AAA growth rates, which included data on a total of 3,768 AAA patients. The patient and AAA characteristics, the details of diameter measurement, and the association between BMI and AAA growth rates are summarized in Table 1 In a prospective study by Burillo et al [13], 122 male patients with a >30 mm AAA were scanned annually with a mean observation time of 8.1 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of them, we identifi ed seven eligible studies [9][10][11][12][13][14][15] reporting the association of BMI and AAA growth rates, which included data on a total of 3,768 AAA patients. The patient and AAA characteristics, the details of diameter measurement, and the association between BMI and AAA growth rates are summarized in Table 1 In a prospective study by Burillo et al [13], 122 male patients with a >30 mm AAA were scanned annually with a mean observation time of 8.1 years.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis by Li et al [17] of three epidemiological studies also showed that claudication was a risk factor for AAA (OR, 3.00; 95% CI, 1.74 to 5.19). However, although the association of PAD with AAA growth is still debated, PAD may be not [12] or even negatively [9,19] associated with AAA growth despite its positive association with AAA presence [16,17]. Bhak et al [12] found no independent association between claudication and AAA expansion rates (adjusted MD, -0.1 mm/year; 95% CI, -0.6 to 0.3 mm/year; P = 0.52).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another recent (published in 2013) meta-analysis by Li et al 2 of three epidemiological studies also showed that CAD was a risk factor for AAA (OR, 1.82; 95% CI, 1.65 to 2.00). Despite the evidence for the positive association of CAD with AAA presence, however, CAD may be not 3 or even negatively 4 associated with AAA growth. Using a large clinical database from the ADAM (Aneurysm Detection and Management) study, Bhak et al 3 found no association between angina or CAD and AAA expansion rates.…”
Section: Introductionmentioning
confidence: 84%